Efektifitas Pembelajaran IPS Terpadu Pasca Pandemi Covid-19 Di MTs Al-Khairaat Pandere Kabupaten Sigi - Yustia, Sri; Khairuraziq (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2023)
This study aims to determine the effectiveness of integrated social studies learning after the Covid-19 pandemic at MTs Al-Khairaat Pandere. The informants in this study were 5 people, namely the principal, social studies teacher and 3 students of class VIII. Data collection techniques include three stages, including observation, interviews with informants and documentation Based on the results of the research that has been done, it can be concluded that the learning method used to increase the effectiveness of student learning works by adjusting class hours and using the quiz method to increase student interest. While the increase in student interest and motivation can be seen from the enthusiasm of students in accepting the learning process. There is an increase in student interest and motivation affecting the final grades of students who increase. This relates to student learning completeness where the average value of students who were previously 78 during the online learning process became 86 with the lowest score obtained by students 74.